The Influence of Guided Discovery Learning Assisted by Fractional Wheels and Learning Motivation on Improving The Critical Thinking Skills of Grade V Students at SD Negeri 1 Dagan Purbalingga - Erlin Susanti; Ristiana Dyah Purbandari (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
The purpose of this research is to examine how employing Guided Discovery Learning tools alongside fractional wheels, as well as enhancing learning motivation, impacts the enhancement of critical thinking abilities among elementary school students. Essential 21st-century skills include critical thinking, digital literacy, information literacy, media literacy, and proficiency in information and communication technology. The goal of mathematics education is for students to develop logical, critical, analytical, meticulous, and responsible abilities. Mathematics and critical thinking are intrinsically linked, as mathematics is understood through critical thinking, and critical thinking is trained through mathematics. Students with strong critical thinking skills can solve problems effectively, preparing them to face real-world challenges and global competition in the 21st century. The research method used is quantitative descriptive research with a correlational approach. Data analysis involved statistical methods, including multiple regression analysis and partial tests (t-tests). The regression analysis F-test indicates that Guided Discovery Learning and learning motivation simultaneously have a significant effect on students' critical thinking. The first partial t-test shows that Guided Discovery Learning impacts critical thinking, and the second t-test indicates that learning motivation influences critical thinking. Based on these results, the Guided Discovery Learning method supported by fractional wheels and enhanced learning motivation significantly improves students' critical thinking patterns.